Selective ortho-methylation of phenol with methanol over copper manganese mixed-oxide spinel catalysts - Reddy, A. Satyanarayana; Gopinath, Chinnakonda S.; Chilukuri, Satyanarayana V. (Journal of Catalysis, 2006)
Methylation of phenol with methanol as an alkylating agent to produce 2,6-xylenol was investigated over copper manganese mixed oxide spinels, CuxMn3-xO4 (x = 0, 0.25, 0.5, 0.75, and 1) prepared through co-precipitation. The catalytic activity strongly depends on the composition, acid-base properties, and structural stability. Various parameters, including catalyst composition, reaction temperature, feed composition, and durability of the catalyst during methylation, were investigated. Mainly o-cresol and 2,6-xylenol, along with small amounts of mesitol, were found in the product. A high ortho-selectivity of 100%, with 2,6-xylenol selectivity of 74%, was observed over Cu0.25Mn2.75O4 at 673 K. These catalysts were investigated using various techniques, including BET surface area, XRD, DRS UV-vis, TPD of NH3 and CO2, TPR, and X-ray photoemission spectroscopy (XPS). Powder XRD of the catalysts revealed the formation of copper-manganese spinels with hausmannite (Mn3O4) tetragonal structure, for x = 0-0.5, whereas an increase in copper content (x > 0.5) led to the formation of cubic Cu1.5Mn1.5O4 phase. DRS UV-vis, and FTIR further supported the changes in structural phases observed by XRD. Temperature-programmed desorption Of CO2 and NH3 showed that the catalysts have strong basicity along with weak acidity when x = 0 and 0.25. XPS and XAES analysis revealed the presence of only Cu2+ ions in fresh sample with x = 0.25, whereas for x = 1.0, both Cu1+ and Cu2+ were observed. The deactivation of the catalysts is attributed to structural changes occurring during the reaction. Catalytic activity is correlated with structure, as well as with acid-base properties. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: 2; 6-xylenol; acidity-basicity; copper-manganese oxides; ortho-alkylation; phenol methylation; Spinels

Copper-based catalysts for water gas shift reaction: influence of support on their catalytic activity - Pradhan, S.; Reddy, A. Satyanarayana; Devi, R. N.; Chilukuri, Satyanarayana V. (Catalysis Today, 2009)
Three copper containing catalysts supported on ceria and mixed oxides of ceria with zirconia and titania were prepared by co-precipitation method and their catalytic activity was tested for water gas shift (WGS) reaction. High surface area (>100m(2)/g) mixed oxides were obtained following the present method of preparation. The catalysts were characterized by XRD, H(2)-temperature programmed reduction (TPR), UV-vis and XPS. Catalytic activity was evaluated for water gas shift reaction in the 200-400 degrees C temperature range, The gas hourly space velocity was varied from 5000 to 25,000h(-1) for better evaluation and comparison of their performance. The effect of CO(2) in the feed gas mixture on the WGS activity of these catalysts was also studied. Among the three catalysts studied, CuO-CeO(2)-ZrO(2) mixed oxide shows better activity, implying the influence of support. Characterization of the catalysts after WGS reaction was also carried out in order to investigate structure-property correlation. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: ceria; Ceria-titania; Ceria-zirconia; Co-precipitation; Copper; Water gas shift